Pengaruh Audit Tenure, Komite Audit, dan Audit Delay terhadap Auditor Switching - Rahayu Surya Bakar; Efrizal Syofyan (Universitas Negeri Padang, 2023)
This research aimed to examine the effect of audit tenure, audit committee, and audit delay on auditor switching. The population in this research are all infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange in 2016-2021. The sampling technique used the purposive sampling. Total sample are 108 companies. The statistical method used logistic regression analysis. The result showed that audit tenure, audit committee and audit delay had no influence on auditor switching in infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange in 2016-2021.